Changing conceptions of national biography : the Oxford DNB in historical perspective - Thomas, Keith, 1933- (Cambridge University Press, 2005)
The publication of the Oxford Dictionary of National Biography in September 2004 was an event of great literary and scholarly importance. In his Leslie Stephen Lecture, commemorating the founder of the original Dictionary of National Biography, the celebrated historian Keith Thomas surveys the many earlier attempts at collective biography, considers the relationship of the Oxford DNB to them, and offers a preliminary assessment of the Oxford DNB itself. The author, who has been chairman of the Supervisory Committee of the Oxford DNB since its inception, writes with intimate knowledge of the project. This Leslie Stephen Lecture complements the earlier Lecture on the DNB by the late Colin Matthew, Founder-Editor of the Oxford DNB, and published by Cambridge in 1997.